Formação de eletrodepósitos de cádmio, síntese e aplicação em fotocatálise de óxido nanoparticulado de cádmio e óxidos de níquel, cádmio, cobalto e ferro a partir de baterias exauridas de Ni-Cd - Moreira, Thamyres Fernandes Messa (2016)
The recycling of Ni-Cd batteries exhausted is important for environmental, scientific and economic reasonsand canbe performed mainly by pyrometallurgical and hydrometallurgical processes.In this work, were developed hydrometallurgicalroutesfor the recycling of positive and negative electrodes of Ni-Cd batteries.Negative electrode was leached with sulfuric acid (H2SO4) 0.50 mol L-1and the positive electrode in citric acid (C6H8O7) 0.50 mol L-1. The main objective of this work is the synthesis and characterization of metallic cadmium film, cadmium oxide and nickel, cadmium, cobalt and iron oxide. Cadmium metal films were formed with the galvanostatic technique under conditions: current density of -28 mA cm-² and charge density ranging at 11.4 C cm-2and 28.4 C cm-2, current density -56 mA cm-2and charge density of 11.4 C cm-2and 28.4 C cm-2.The maximum deposition efficiency of cadmium reached 84.87% and the reaction of hydrogen evolution occurs in the system while reducing the cadmium. Synthesis of cadmium oxide (CdO) was carried from the thermal treatment of the precursor of cadmium carbonate (CdCO3). The obtained CdO has an average crystallite size of 22.21 nm and was characterized by infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The metal oxide synthesized by sol-gel method had mixed composition containing nickel oxide (NiO), CdO, cobalt oxide (Co3O4) and iron oxide (Fe2O3) being called the NiO/CdO/Co3O4/Fe2O3and characterized by FT-IR, XRD, SEM, X-ray spectroscopy for energy dispersion (EDX), TEM and optical emission spectrometry with inductively coupled plasma (ICP OES).The synthesized oxide wasapplied in degradation process of a textile dye Reactive Black V-2B. The CdO oxides and NiO/CdO/ Co3O4/ Fe2O3showed catalytic behavior and efficiencyof degradationdoes not depend on pH.The highest dye degradation efficiency obtained for the CdO was 67.10% and the NiO/CdO/Co3O4/Fe2O386.30% after 480 minutes of analysis